On the existence of stable equilibrium points in delayed cellular neural networks - Arslan, Emel; Arik, Sabri; Tavsanoglu, Vedat (IEEE, 2006)
This paper presents new sufficient conditions for the existence of stable equilibrium points in the total saturation region for delayed cellular neural networks (DCNNs). The obtained results are compared with the previous results derived in the literature. It is also shown that the results of this paper generalize the previous literature results for the existence of stable equilibrium points for DCNNs. It is also demonstrated by a numerical example that the conditions derived for existence of a stable equilibrium point may not always guarantee the complete stability of a delayed cellular neural network.
Keywords: delayed cellular neural networks; complete stability; STABILITY; Computer Science; Imaging Science & Photographic Technology